Small-angle neutron scattering and fluorescence quenching studies of aggregated ionic and nonionic surfactants in the presence of poly(1,4-diaminobutane) dendrimers - Li, Y; McMillan, C; Bloor, D; Penfold, J; Warr, J; Holzwarth, J; Wyn-Jones, E (ACS, 2000)
Small-angle neutron scattering (SANS) measurements were carried out on the supramolecular complexes formed between sodium dodecylsulfate (SDS) and different generation poly(1,4-diaminobutane) dendrimers. For the first and second generation dendrimers, the scattering data are consistent with the existence of spherical SDS micelles bound to the dendrimers. The aggregation numbers of these bound micelles were determined. When these data are combined with reported data from binding isotherms, information on the molecular composition and structure of the complexes can be obtained. For the first generation dendrimers the complexes comprise three and four dendrimer molecules bound to an SDS micelle. The number of bound dendrimers decreases for the next generation poly(1,4-diaminobutane) dendrimers. The SANS data for the dendrimer/SDS complexes of the third and fourth generation dendrimers are not consistent with small spherical micelles. Indeed the intense scattering observed at low values of wave vector transfer is consistent with the formation of large aggregates. This result was confirmed from viscosity measurements. Fluorescence quenching measurements suggest that the bound SDS in these larger structures have aggregation number of twice those of normal SDS micelles. The overall data suggests that the basic building blocks in these complexes consists of surfactant aggregates linking different dendrimers. Finally SANS measurements were also carried out to study the micelles of hexaethyleneglycol monododecyl ether (C12EO6) in the presence of these dendrimers. The scattering data are consistent with spherical free C12EO6 micelles existing in solution.